A gender financing gap: fake news or evidence?. Issue 2 (2nd April 2020) - Aernoudt, Rudy; De San José, Amparo
ABSTRACT: Women-led businesses are less likely to raise venture capital than male-only businesses and the amounts that they raise are lower. Yet women-led businesses deliver better revenue performance and return on investment. So why are venture capitalists reluctant to invest in women-led businesses? One reason is that women entrepreneurs are over concentrated in sectors that are less attractive to investors and have a low presence in technology sectors. Another reason is the lower propensity of women entrepreneurs to seek venture capital. However, women who do approach venture capital funds are almost as likely as men to be successful in raising finance. Moreover, women-led businesses perform well in raising follow-on finance. And women business angels – a minority of all business angels – have a clear propensity to invest in women founders.